PERAN METODE DISKUSI DALAM MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN IPS - Sri Mulyati; Tetep; Lili Dianah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the role of the discussion method in developing students’ critical thinking skills in social studies learning, to identify its strengths and weaknesses, and to explain its suitability with the characteristics of social studies instruction. This research employs a qualitative approach using a library research method. The data were obtained from books, journal articles, and various scientific publications relevant to the discussion method, critical thinking, and social studies learning. Data were collected through documentation study and analyzed using descriptive qualitative techniques by reviewing, comparing, and synthesizing information based on the research focus. The results show that the discussion method plays an important role in developing students’ critical thinking skills as it encourages active participation, the ability to express opinions, respond to others’ viewpoints, and construct logical arguments. This method also has advantages in enhancing creativity, communication skills, collaboration, and learning motivation. However, its implementation faces several limitations, such as requiring more time, uneven student participation, and dependence on the teacher’s ability to manage the discussion effectively. Therefore, the discussion method can be considered a relevant instructional strategy to support the development of students’ critical thinking skills in social studies learning.